Space Solar Power: A Sustainable Solution or an Environmental Dilemma? - Acquarone, Camila; Rotola, Giuliana; Yakushina, Yana (Central European Academy Law Review, 2025)
Space-Based Solar Power (SBSP) involves collecting solar energy in space and transmitting it to Earth, ensuring continuous power generation. Though an old concept, SBSP is gaining renewed interest, with projects such as the European Space Agency’s (ESA) SOLARIS targeting deployment by 2030. Consulting firms have confirmed its cost-benefit viability. However, numerous legal, economic, and regulatory challenges arise. Key questions include space environmental considerations, such as orbital light pollution, as well as ground-based environmental concerns, particularly regarding the size of the rectenna required to capture space laser beams. The deployment of massive SBSP systems could also contribute to an increase in space debris if the maintenance and decommissioning of such large structures are not addressed during the design phase. Beyond environmental aspects, the commercialisation of SBSP raises issues concerning the ESA’s role as an energy producer, the impact of facility location on energy resale, and the classification of space solar energy or orbital slots for SBSP installation as space resources. These considerations will raise challenges regarding the ownership and business model of the energy produced, in accordance with the provisions of the Outer Space Treaty. International energy distribution presents additional complexities, particularly in ensuring equitable access for developing nations. Within the European Union, SBSP integration would require significant grid upgrades, pose the risk of market saturation, and necessitate navigating diverse national regulations. Despite its transformative potential, SBSP faces significant legal, technical, and economic challenges, all of which are explored in this paper, inviting a transversal and comprehensive reflection.